Copy of An Abnormal Course of the Internal Carotid Artery in the Neck - Ocalan, Ramazan; Ceyda Akin Ocalan, Fatma; Korkmaz Disli, Zeliha; Ozlugedik, Samet; Unal, Adnan (Annals of Medical Research, 2021)
Internal carotid artery anomalies are extremely rare and may cause unexpected complications during surgery. The magnetic resonance imaging of the neck of a 83-year old patient was admitted to the ear,nose, and throat clinic with a mass in the neck, which was reported to be a giant mass lesion in the right side of the neck, inferior of the angle of mandible, to the anterolateral of the sternocleidomastoid muscle. After the fine needle aspiration biopsy the patient was thought to be a malignant melanoma case, making us plan chemoradiotherapy after the surgery. During the radical neck dissection, while the surface of the internal carotid artery was being dissected superiorly, it was noticed that the artery was springing abnormally in the form of the siphon posteriorly. Although these types of anamolies are rare variations, they can cause serious life-threatening complications during neck surgery.
Keywords: Carotid Artery; Neck; Complications